Influence of Ability and Motivation on Performance Through Organizational Culture on Tutor Paket C SKB in Indonesia - Estafianto, Hary Dwi; Fakhruddin, Fakhruddin; Sutarto, Joko (Universitas Negeri Semarang, 2020)
Tutor performance is very influential on the level of success in achieving the objectives of implementing equality education, The purpose of this study is to analyze and describe the direct and indirect effects of ability, motivation, and organizational culture on the performance of tutors Paket C SKB in Central Java Indonesia. This study uses a quantitative associative research design. The respondents of this study were tutors of equality education in the area of Central Java which number were 185 respondents in total by using a proportional stratified random sampling technique. The data collection technique used was a questionnaire. The data analysis technique was using SPSS 23.0 software. The results showed that the ability, motivation, and organizational culture had a positive and significant direct effect on tutor performance, the ability and motivation have an indirect and positive and significant effect on tutor performance through organizational culture. This research concludes that organizational culture mediates the influence of ability and motivation on the performance of tutors Paket C SKB in Central Java. This research provides knowledge to non-formal education institutions in improving the performance of tutor Paket C, needing to pay attention to agility, motivation, and culture organization.